
6-3t=-5+2t怎么算?
11个回答
展开全部
6-3t=5+2t
6-5=2t+3t
5t=1
t=1/5
t=0.2
6-5=2t+3t
5t=1
t=1/5
t=0.2
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
6-3t=-5+2t怎么算?
2t+3t=6+5
5t=11
t=11/5
望采纳 谢谢~~
2t+3t=6+5
5t=11
t=11/5
望采纳 谢谢~~
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
6-3t=-5+2t
5t=11
t=2.2
5t=11
t=2.2
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
6一3t=一5+2t
6+5=2t+3t
5t=11
t=5.5。
6+5=2t+3t
5t=11
t=5.5。
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
6-3t=-5+2t怎么算?
2t+3t=6+5
5t=11
t=11/5
2t+3t=6+5
5t=11
t=11/5
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询